ASSOCIATION BETWEEN ESTROGEN LEVELS WITH INTRAOCULAR PRESSURE IN PRIMARY OPEN ANGLE GLAUCOMA PATIENT: Oral Presentation - Observational Study - Resident - Rambe, Alvin; Sari, Masitha Dewi; Aldy, Fithria; Ashar, Taufik (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesThere are studies that state that estrogen deficiency can exacerbate visual disturbances in glaucomapatients. To determine the relationship between estrogen levels and intraocular pressure (IOP) inpatients with POAG. MethodsThis study used a case-control design in 30 POAG patients who came to the OphthalmologyPolyclinic at the University of North Sumatra Hospital and Network Hospital. The data collectionmethod in this study used a consecutive sampling technique starting from February 2022 until thesample was filled. The inclusion criteria in this study were all women with POAG who were ?40years old and willing to be the research sample. The exclusion criteria for this study were patientswith a history of secondary glaucoma or a history of optic nerve disease, a history of ocular surgery(except cataracts), a history of orbital trauma, menstrual disorders, or currently on hormonaltherapy, a history of systemic or autoimmune disease. Data is then collected and analyzed. ResultsOf the 30 patients with POAG, the majority were aged 45-65 years (46.7%) with an average age of55.87(±12.91) years and had suffered from POAG for an average of 1.62(±2.08) years. The averagepatient had an intraocular pressure of 25.07(±6.12) mmHg, MD -12.99(±8.28) dB, VCDR0.78(±0.13) mm, and estrogen levels 2.47(±2.11) pg/dL. There was no significant relationshipbetween estrogen levels and intraocular pressure (p=0.851). ConclusionThere was no significant association between estrogen levels and intraocular pressure in patientswith POAG.